7u-36=3(u-8)

Simple and best practice solution for 7u-36=3(u-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7u-36=3(u-8) equation:


Simplifying
7u + -36 = 3(u + -8)

Reorder the terms:
-36 + 7u = 3(u + -8)

Reorder the terms:
-36 + 7u = 3(-8 + u)
-36 + 7u = (-8 * 3 + u * 3)
-36 + 7u = (-24 + 3u)

Solving
-36 + 7u = -24 + 3u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-3u' to each side of the equation.
-36 + 7u + -3u = -24 + 3u + -3u

Combine like terms: 7u + -3u = 4u
-36 + 4u = -24 + 3u + -3u

Combine like terms: 3u + -3u = 0
-36 + 4u = -24 + 0
-36 + 4u = -24

Add '36' to each side of the equation.
-36 + 36 + 4u = -24 + 36

Combine like terms: -36 + 36 = 0
0 + 4u = -24 + 36
4u = -24 + 36

Combine like terms: -24 + 36 = 12
4u = 12

Divide each side by '4'.
u = 3

Simplifying
u = 3

See similar equations:

| t^2-60t=-450 | | t^2+60t=-450 | | -3*-3+6+2= | | 14(6x+16)= | | 3*3+6+2= | | 5+7(2b-2b)=5 | | y(25+-.75y)=350 | | x^2+y^2+6x-14y+42=0 | | 42-21x=63-7y | | (6xy+7)dx+(3x^2-2)dy=0 | | 6x+9-x+19= | | 4x+10=-42-8x | | 3n=34 | | 17x-2x=7x+11 | | 7x+13=3x+65 | | 4x+38=180 | | 2(x-3)(x-3)+3=13 | | 2(x-3)+3=13 | | x^4-x^3-2x^2+4x-24=0 | | (X^2+24)= | | 3x^2-11x-3=-x^2 | | Un=5+(0.1n-0.1) | | Un=5+(0.1n+0.1) | | Cos(5x)-cos(9x)=0 | | z^2-(3-2i)z+(5-5i)=0 | | 6x=n+4 | | 4x^2+12x+9=49x | | 4x^3+12x+9=49x | | -6.8(7.9+1.2*-7.3)+3.7=4.2*-7.3+40.90016 | | 1/8+2/3= | | 1/3+2/3= | | 5y+11=6 |

Equations solver categories